2018
DOI: 10.4172/2168-9784.1000273
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Ultrasound as a Diagnostic Tool for Breast Cancer in the Screening of Younger Women (Age 25-38) in Guyana

Abstract: Objective: Ultrasound is used in many ways, not only as an initial diagnostic tool for confirmation of pathology determined from biopsies of the breast but also staging of breast cancer. Ultrasound is inexpensive and readily available almost all over the country. In a recent publication from the UK, the incidence of breast cancer in women younger than 35 years was 1.4% and in those younger than 30 years it was 0.43%. Breast Cancer is the most commonly diagnosed cancer amongst women worldwide. There were approx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…Our results matched with Nandan et al [31], a retrospective study that focused on charts from the Cancer Institute of Guyana to assess the role of ultrasound in screening young women. They concluded that ultrasonography is effective and sensitive in the diagnosis of breast cancer.…”
Section: Discussionsupporting
confidence: 88%
“…Our results matched with Nandan et al [31], a retrospective study that focused on charts from the Cancer Institute of Guyana to assess the role of ultrasound in screening young women. They concluded that ultrasonography is effective and sensitive in the diagnosis of breast cancer.…”
Section: Discussionsupporting
confidence: 88%
“…Sonoelastography is a valuable tool in this regard as it can be used to detect malignant breast lesions in an incipient state, potentially improving patient prognosis. Another characteristic of young women is that they tend to exhibit dense breasts [63,64], a feature that is compatible with evaluation by sonoelastography.…”
Section: Discussionmentioning
confidence: 78%
“…Furthermore, it is more reliable than mammography in detecting cancers in dense breasted women and the distinction between cystic and solid lesions can be made. Also, malignant lesions are recognized with 98% confidence [1].…”
Section: Introductionmentioning
confidence: 99%
“…3D US breast acquisitions would overcome these limitations: larger ROIs can be imaged, arbitrary cross-sections of this ROI are possible, and measurements of the size and 1 are affiliated with the Robotics and Mechatronics group, University of Twente, The Netherlands m.k.welleweerd@utwente.nl 2 is affiliated with the Bio-mechatronics and Energy-Efficient Robotics group, ITMO University, St. Petersburg, The Russian Federation.…”
Section: Introductionmentioning
confidence: 99%